Assessment of precipitation behavior in dental castings of a Co–Cr–Mo alloy. (October 2015) - Yamanaka, Kenta; Mori, Manami; Chiba, Akihiko
Abstract: This study investigated solute portioning and precipitation in dental castings of a Co–Cr–Mo alloy and discussed their effects on alloy performance, in particular, the mechanical properties. Samples of a commercial Co–29Cr–6Mo (mass%) alloy were prepared using a dental-casting machine. The precipitates formed owing to the partitioning behaviors of the alloying elements were investigated using scanning electron microscopy, electron backscatter diffraction analysis, electron probe microanalysis, and transmission electron microscopy. The prepared samples exhibited a very coarse face-centered-cubic γ -phase dendritic structure with an average grain size of a few millimeters. A large number of precipitates, which decomposed further into complex interdendritic constituents ( σ - and M23 C6 carbide phases) were observed in the interdendritic regions rich in Cr, Mo, Si, and C. A reaction between the σ -phase and carbon is probably responsible for the carbide M23 C6 ; however, this reaction did not occur to completion in the current case in spite of slow cooling (i.e., long exposure to elevated temperatures) in dental casting. While these precipitates result in high strength (hardness) and/or brittleness, the properties can be improved further by optimizing the alloy composition and the manufacturing process. The results of this study shed light on the significance of precipitation control in dental castings of Co–Cr–Mo alloys and should aid in the design of novel biomedical Co–Cr-based dental alloys that exhibit better performances. Highlights: We study solute portioning and precipitation in dental castings of Co–Cr–Mo alloy. This is done to determine their effects on the mechanical and corrosion properties. The alloy microstructure consists primarily of a face-centered-cubic γ -phase Precipitates are observed in the interdendritic regions rich in Cr, Mo, Si, and C. Reaction between the σ -phase and carbon is responsible for the carbide M23 C6 .